FRoG: a fast robust analytical dose engine on GPU for p, 4He, 12C and 16O particle therapy - Mein, Stewart (2020)
Radiotherapy with protons and heavier ions landmarks a novel era in the field of highprecision cancer therapy. To identify patients most benefiting from this technologically demanding therapy, fast assessment of comparative treatment plans utilizing different ion species is urgently needed. Moreover, to overcome uncertainties of actual in-vivo physical dose distribution and biological effects elicited by different radiation qualities, development of a reliable high-throughput algorithm is required. To this end, we engineered a unique graphics processing unit (GPU) based software architecture allowing rapid and robust dose calculation. Fast dose Recalculation on GPU (FRoG) currently operates with four particle beams, i.e., raster-scanning proton, helium, carbon and oxygen ions. Designed to perform fast and accurate calculations for both physical and biophysical quantities, FRoG operates an advanced analytical pencil beam algorithm using parallelized procedures on a GPU. Clinicians and medical physicists can assess both dose and dose-averaged linear energy transfer (LET) distributions for proton therapy (and in turn effective dose by applying variable RBE schemes) to further scrutinize plans for acceptance or potential re-planning purposes within minutes. In addition, various biological model predictions are readily accessible for heavy ion therapy, such as the local effect model (LEM) and microdosimetric kinetic model (MKM). FRoG has been extensively benchmarked against gold standard Monte Carlo simulations and experimental data. Evaluating against commercial treatment planning systems demonstrates the strength of FRoG in better predicting dose distributions in complex clinical settings. In preparation for the upcoming translation of novel ions, case-/disease-specific ion-beam selection and advanced multi-particle treatment modalities at the Heidelberg Ion-beam Therapy Center (HIT), we quantified the accuracy limits in particle therapy treatment planning under complex heterogeneous conditions for the four ions (p, 4He, 12C, 16O) for various dose engines, both analytical algorithms and Monte Carlo code. Devised in-house, FRoG landmarks the first GPU-based treatment planning system (non commercial) for raster-scanning 4He ion beams, with an official treatment program set for early 2020. Since its inception, FRoG has been installed and is currently in operation clinically at four centers across Europe: HIT (Heidelberg, Germany), CNAO (Pavia, Italy) , Aarhus (Denmark) and the Normandy Proton Therapy Center (Caen, France). Here, the development and validation of FRoG as well as clinical investigations and advanced topics in particle therapy dose calculation are covered. The thesis is presented in cumulative format and comprises four peer reviewed publications.